Effect of drying on the physical and chemical properties of palm kernel oil - Habibiasr, Mina; Mokhtar, Mohd Noriznan; Ibrahim, Mohd Nordin; Md Yunos, Khairul Faezah; Ibrahim, Nuzul Amri (Wiley, 2021)
Background: Palm kernel is the edible seed of the oil palm fruit obtained during the palm oil milling process. For efficient processing and storage, the moisture content of palm kernel must be reduced to an optimal level by drying. This study aimed to see how drying influenced the physical structure and physicochemical properties of palm kernel and oil. Before and after drying, the free fatty acid (FFA), color, fatty acid composition, Fourier transform infrared, thermal properties and structure of palm kernel were investigated. Results: Results show that drying significantly (P < 0.05) reduced FFA and color of palm kernel oil. Drying also significantly affected (P < 0.05) composition of some fatty acids in palm kernel oil such as capric acid, lauric acid, myristic acid, palmitic acid and oleic acid. However, drying did not affect palm kernel and palm kernel oil functional groups and thermal properties. After drying, structural damage of palm kernel was observed. Conclusion: Based on these findings, the quality of kernel oil may be maintained after drying, and it can even be improved based on lower FFA content. © 2022 Society of Chemical Industry.